2008
DOI: 10.1103/physreve.77.031131
|View full text |Cite
|
Sign up to set email alerts
|

Rectification in synthetic conical nanopores: A one-dimensional Poisson-Nernst-Planck model

Abstract: Ion transport in biological and synthetic nanochannels is characterized by phenomena such as ion current fluctuations and rectification. Recently, it has been demonstrated that nanofabricated synthetic pores can mimic transport properties of biological ion channels [P. Yu. Apel, et al., Nucl. Instr. Meth. B 184, 337 (2001); Z. Siwy, et al., Europhys. Lett. 60, 349 (2002)]. Here, the ion current rectification is studied within a reduced 1D Poisson-Nernst-Planck (PNP) model of synthetic nanopores. A conical ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
119
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 35 publications
2
119
0
1
Order By: Relevance
“…For instance, entropic effects on the rectification efficiency of the conical nanopores of Siwy and co-workers have been analyzed by Kosinska et al ͑2008͒. However, in-pore diffusion in a liquid suspension requires a fully 3D analysis of the pumping mechanism, which sets the basis for the fabrication of more complicated ionic devices ͑Stein et van der Heyden et al, 2004͒.…”
Section: B Artificial Nanoporesmentioning
confidence: 99%
“…For instance, entropic effects on the rectification efficiency of the conical nanopores of Siwy and co-workers have been analyzed by Kosinska et al ͑2008͒. However, in-pore diffusion in a liquid suspension requires a fully 3D analysis of the pumping mechanism, which sets the basis for the fabrication of more complicated ionic devices ͑Stein et van der Heyden et al, 2004͒.…”
Section: B Artificial Nanoporesmentioning
confidence: 99%
“…The entropic nature of this term leads to a genuine dynamics which is distinctly different from that observed when the potential is of energetic origin [17]. It has been shown that the FJ equation can provide a very accurate description of entropic transport in channels of varying cross-section [17,18,19]. However, the derivation of the FJ equation entails a tacit approximation: The particle distribution in the transverse direction is assumed to equilibrate much faster than in the main (unconstrained) direction of transport.…”
Section: Introductionmentioning
confidence: 99%
“…The driven transport of charged particles across bottlenecks (Burada et al 2009), such as ion transport through artificial nanopores or artificial ion pumps (Siwy et al 2005;Kosinska et al 2008) or in biological channels (Berezhkovskii & Bezrukov 2005), are more familiar systems where diffusive transport is regulated by entropic barriers. Similarly, the operation of artificial Brownian motors and molecular machines also relies on a mutual interplay among diffusion and binding action by energetic or, more relevant in the present context, entropic barriers (Derenyi & Astumian 1998;Astumian & Hänggi 2002;Reimann & Hänggi 2002;Burada et al 2009;).…”
Section: Introductionmentioning
confidence: 99%